Sex and Age Matter - Mazurana, Dyan; Benelli, Prisca; Gupta, Huma; Walker, Peter (Tufts Archival Research Center, 2005)
Humanitarian aid is largely guided by anecdotes rather than evidence. Currently, the humanitarian system shows significant weaknesses in data collection, analysis and response in all stages of a crisis or emergency. As a result, the present humanitarian system is much less evidence-driven than it should be and than it would like to be. To ensure that vulnerabilities, needs and access to life-saving services are best understood and responded to, humanitarian actors must collect information based on sex and age. When this data is lacking, it limits the effectiveness of humanitarian response in all phases of a crisis.